Strategies for the management and conservation of plant species for human and animal consumption, which promote the protection of natural resources in the dry and humid tropical forest of zone one of Ecuador - Albuja Montenegro, Alexis Zahir; Caicedo Rosero, Diego Marcelo; Benavides Rosales, Hernán Rigoberto; Peña Chamorro, Julio Jairo; Sanchez Figueroa, Martha Alexandra (Tierra Infinita, 2022)
The objective of this research was to know the properties of flora with food uses for the human and animal species that exists in the Awá and Afro communities, in order to encourage the maintenance of dry and humid tropical forest ecosystems in zone one to promote food security. A fieldwork was carried out that facilitated the collection of data, obtaining a priority list of plant species described in technical sheets, which allowed determining the habitat and its botanical characterization; identified materials and a physical space to create a botanical garden with priority species, managed the acquisition and planting of plant species, a drip irrigation system, labeling of plant species and the initial management of the botanical garden. The database prioritized 106 plant species of food use that served for the establishment of the botanical garden located in the experimental center "Alonso Tadeo" of the Universidad Politécnica Estatal del Carchi (UPEC); the implemented species are identified by informative signs, where you can scan a QR code that allows you to visualize the botanical characterization, importance and use of them. It is concluded that one of the main purposes of botanical gardens is to preserve species that guarantee food security by conserving species of food and medicinal use that can be exploited by communities